(untitled) (Journal of Environmental Science Studies, 2018)
The quality of water used for domestic purposes from three boreholes in Wudil Local Government (KUST Wudil, Unguwar Danya and Unguwar Fulani) was analyzed and assessed for a period of five weeks using standard methods of sampling and laboratory analysis. Parameters tested include pH dissolved oxygen (DO), five-day biochemical oxygen demand (BOD ), nitrate ion (NO ), conductivity, hardness, temperature total dissolved 5 3 solids (TDS) and turbidity. Results showed that there are significant differences between the different wards. However, a one way ANOVA conducted reveals significant difference (p < 0.05) between the different sites and physicochemical parameters. It is therefore recommended that government should be more effective in controlling the point source of pollution in the area.